2006
DOI: 10.1103/physrevd.74.014013
|View full text |Cite
|
Sign up to set email alerts
|

PossibleS-wave bound-states of two pseudoscalar mesons

Abstract: Using the potentials derived from vector-meson-exchanges, the KK, DK, BK, DD, BB, BD ,DK, BK and BD systems are studied. Possible S-wave bound-states of two pseudoscalar mesons are discussed. We find that systems of DB, DD, BB and DK with isospin 0 are likely to form S-wave bound states via strong interactions while the others are unlikely to be bound by the strong interaction sector alone. With the Coulomb potential, the K + K − system can form an atomic bound state -the kaonium. The influence of the one-meso… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
80
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(86 citation statements)
references
References 40 publications
5
80
0
1
Order By: Relevance
“…[3] it was shown that the bump was better interpreted in terms of a DD molecular state, below the DD threshold (so called X(3700)), that had been predicted in Ref. [4] and has also been found theoretically in other works [5][6][7][8][9]. Similarly, in Ref.…”
Section: Introductionmentioning
confidence: 92%
“…[3] it was shown that the bump was better interpreted in terms of a DD molecular state, below the DD threshold (so called X(3700)), that had been predicted in Ref. [4] and has also been found theoretically in other works [5][6][7][8][9]. Similarly, in Ref.…”
Section: Introductionmentioning
confidence: 92%
“…In this sense, a bound state of DD was theoretically found in [6] and tentatively called X(3700). Other works have also reported on this possibility [7][8][9][10][11][12]. Subsequently, experimental support for such a state was found in [13] from a bump close to the threshold of the DD invariant mass distribution in the e + e → J/ψDD reaction [14].…”
Section: Introductionmentioning
confidence: 93%
“…We should also note that with a different formalism using the Schrödinger equation with one vector-meson exchange potential, D D states also appear for some choices of a cutoff parameter in [48].…”
Section: Comparison With Other Workmentioning
confidence: 99%